Kajian Penerapan Sistem Keselamatan dan Kesehatan Kerja (K3) pada Proyek Pembangunan Gedung Fasilitas Kesehatan (Proyek X) di Kabupaten Fakfak - Jusmawandi Jusmawandi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
The construction sector is an industry with a high level of work accident risk due to its dynamic and complex work characteristics. This study aims to examine the application of the Occupational Health and Safety (OHS) System and evaluate its effectiveness in mitigating risks at the Health Facility Building Construction Project (Project X) in Fakfak Regency. The research method used is a descriptive-analytical quantitative approach with purposive sampling of 25 respondents, including executors, supervisors, and field workers. Risk analysis was conducted using the Failure Modes and Effects Analysis (FMEA) method by measuring Severity, Occurrence, and Detection parameters to produce a Risk Priority Number (RPN). The results show that RPN values range from 52.35 to 452.30. The highest risk was found in the variable of limited safety signage in hazardous locations (RPN 452.30), which falls into the very high category. Additionally, 10 high-risk variables and 9 medium-risk variables were identified, dominated by technical, operational, and management factors, such as the use of heavy equipment by uncertified operators and weak implementation of Standard Operating Procedures (SOP) and OHS audits. This study concludes that the application of OHS in Project X is still reactive and requires strengthening risk-based safety management systems as well as improving workforce competence to achieve zero accident conditions.